Incidências da privatização da educação na BNCC: do direito à educação ao direito à aprendizagem - Silva, Deive Bernardes da (2022)
The present thesis entitled Incidence of the Privatization of Education at BNCC: from the Right to Education to the Right to Learning is part of the research line State, Policies and Management of Education, of the Graduate Program in Education of the Faculty of Education of the Federal University of Uberlândia (UFU). The main objective of the study is to analyze the dimensions of the privatization of Basic Education in Brazil around the construction and approval of the National Common Curricular Base, which gives parameters for school curricula in the present time, specifically problematizing the right to education with the right to learning and its implications for educational principles and legal-normative dimensions. This process touches different contexts, especially in the governments that succeeded the Constitution of 1988 and that had repercussions on non-constitutional laws such as LDB, PNE and new High School. The analyzes highlight the privatization processes that permeate public education policies in Brazil and, specifically, their relationship with the new configurations of the State from the influence of the New Public Management. This was engendered in the elaboration of the BNCC with the incisive action of the education privatize block, which shares common representatives in MEC, CNE, Consed, Undime and Movimento Pela Base. The investigation relied on the epistemic subsidy of classic works of liberal and Marxist thought and contemporary works concerning the theme, in a historical-dialectical materialist perspective. This is a qualitative research, whose methodology covers bibliographic and documentary analysis, as elements to support the analysis of the main official documents (Law No. 13.005/2014, Law No. 13.415/2017, CNE Opinions, MEC Resolutions, as BNCC) and documents published by members of the privatized block that corroborate the political autonomy of the right to learning. It was found that the Movimento Pela Base, specifically constituted in the face of the BNCC, remains vigilant in its implementation and even with the new High School, consolidating its influence in the educational scenario at the national territory. Among the main interests of the privatized bloc working with the CNE, Consed, Undime and the MEC are to maintain the reputation of the conglomerate that presents “social responsibility” as well as guaranteeing mechanisms for the production of student subjectivities in line with the mercantile logic. In view of the analysis developed, some findings were possible that, within the scope of educational policies, are classified as characterizing the concreteness of the privatize block agenda both before, during and after the BNCC approval and its unfolding in the autonomy of the right to learn, dissociated from the political sense broader right to education, which interests the capital agents. In this direction, the right to learning gains greater normative prominence, depriving itself of the right to education, based on the curriculum policy established by the BNCC, including the insertion of item IX in Article 206 of the Federal Constitution of 1988, through the Constitutional Amendment 108 of 2020, which distinguishes them.